The Implementation of the Merdeka Curriculum Viewed From School Readiness in Lampung Province - Pujiati, Pujiati; Nurdin, Nurdin; Rahmawati, Rahmawati; Pritandhari, Meyta (Economic Education and Entrepreneurship Journal, 2024)
The curriculum is an important part of education. To realize quality human resources, a curriculum that accommodates various competencies and skills is needed. Curriculum changes are necessary to adapt to current needs and prepare for the future. This research aims to understand the implementation of the Merdeka curriculum in terms of school readiness in Lampung Province. This research is a qualitative descriptive study. The research informants include 5 (five) educators from several high schools in Lampung Province. Data collection was conducted using in-depth interviews and observations, supported by literature studies. The research results show that 1) There are still differences in teachers' perceptions regarding the implementation of the Merdeka curriculum due to several differences in understanding, which are suspected to be caused by varying intensities in participating in socialization or experiences in attending activities related to the implementation of the Merdeka curriculum organized by the Education Office or through sharing experiences with colleagues in the MGMP forum, as well as not yet maximizing independent study through various sites facilitated by the Ministry of Education and other internet sources. 2) The school's readiness is good, but there is still a need for improvement in the provision of facilities and budget to maximize learning outcomes. 3) The educators' readiness is good, but supervision is still needed in the implementation of the Program Penguatan Profil Pelajar Pancasila (P5).DOI: http://dx.doi.org/10.23960/E3J/v7.i2.182-189